What makes students feel authentic in an integrated RE classroom?. Issue 2 (3rd April 2018) - Ubani, Martin
Abstract: The focus of this article is on 9th grade students' ( N = 9) perceptions on aspects that make them feel authentic in integrated religious education (RE) lessons among students of various faiths. All of the students had previously studied RE in segregated groups. The data was collected in a collaborative teaching experiment in Finland with student interviews. The students included young people between the ages of 15 and 16 from Lutheran RE, Orthodox RE and ethics instruction. The analysis identified five themes the students reported as having contributed to their sense of authenticity in RE: neutral pedagogical approach, approving social climate concerning diverse beliefs, space for different worldviews in instruction, group composition concerning beliefs and the position of the teacher regarding religion and his/her students.